Report from the scientific conference organized on the occasion of the International Day of Clinical Research and the 35th anniversary of the Bioethics Committee of the Jagiellonian University, Krakow, April 12, 2017. - Smykowski, Krzysztof (Studia Ecologiae et Bioethicae, 2017)
The summary is not available.